The Dynamics of Finding Identity as Feminine Figure in Beautiful Boxer - Wijaya, Maria V. F.; Prihanto, Sutyas; Luik, Jandy (Faculty of Psychology, Universitas Surabaya, 2010)
The Beautiful Boxer Film portrays a man’s life journey who struggles with his gender identity and internal conflict. This man works as a Thailand boxer which is closed with masculinity while he has a feminine soul. This research aims to answer the questions: how is the adaptation process with his gender identity conflict, the role of social support, and coping efforts which was done related to the conflict and the meaning of muay thai for him. Semiotic method was adopted to answer those questions. This research has begun with interpreting the visual codes in several scenes of the movie which reflect any symbols. Highlights in this research are: the man’s life process revealing his struggles to find his identity, the role of social support, the combination of three coping methods (seeking support, restructuring, and taking active steps), and the changing of muay thai value, from economics, personal and virtues to spiritual. Film Beautiful Boxer mengisahkan perjalanan hidup tokoh dengan masalah identitas gender dan pergulatan proses internal yang dialaminya. Tokoh ini mendalami profesi sebagai petinju Thailand yang sarat dengan maskulinitas meskipun memiliki jiwa yang feminin. Pertanyaan penelitian yang akan dijawab adalah Bagaimana dinamika penyesuaian diri tokoh dengan masalah identitas gender yang dialaminya, peran dukungan sosial, usaha coping yang dilakukan terkait konflik yang dialami, dan makna muay thai bagi tokoh. Penelitian dilakukan dengan menggunakan metode semiotika. Penelitian diawali dengan pemaknaan kode-kode visual dalam beberapa adegan film yang dianggap sebagai simbolisasi visual. Beberapa hal yang menonjol dalam kajian ini adalah tahapan kehidupan tokoh yang menjelaskan dinamika penemuan jati dirinya, peran dukungan sosial, perpaduan tiga usaha coping yang dilakukan, yaitu: seeking support, restructuring, dan taking active steps, dan adanya pergeseran nilai muay thai yang berawal dari nilai ekonomis, personal, kemuliaan/virtues, dan kemudian spiritual.